2008
DOI: 10.1016/j.crte.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the ‘Biarez–Favre’ and ‘Burland’ models for the compressibility of remoulded clays

Abstract: This study aims at comparing the prediction by the Biarez and Favre model as well as by the more recent Burland one, established for reconstituted normally consolidated clays submitted to oedometric loading. The former, proposed in the 1970s, uses the liquidity index I L , and while the latter introduces a parameter, I v, which is a normalised void index based on two characteristic void ratios (e à 100 and e à 1000 ) corresponding to the oedometric curve of s 0 v ¼ 100 kPa and s 0 v ¼ 1000 kPa. The aim of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Extensive studies on the index properties of the material have been performed and published by various authors (e.g. Favre & Hattab, 2008;Hattab & Favre, 2010). Identification of the GoG clay properties through the Atterberg limits represented in the (w L -I p ) diagram ( Fig.…”
Section: Clay Properties Gulf Of Guinea Claymentioning
confidence: 99%
“…Extensive studies on the index properties of the material have been performed and published by various authors (e.g. Favre & Hattab, 2008;Hattab & Favre, 2010). Identification of the GoG clay properties through the Atterberg limits represented in the (w L -I p ) diagram ( Fig.…”
Section: Clay Properties Gulf Of Guinea Claymentioning
confidence: 99%
“…12). Favre and Hattab (2008) demonstrated that the difference between the two curves concerns especially clays with high liquidity limits (above 100%), which is the case with GoG's clay.…”
Section: The Burland Intrinsic Compression Line (Icl)mentioning
confidence: 96%
“…The GoG_REM curve (Fig. 3), were e is the void ratio and s' v the vertical effective stress, exhibits the intrinsic compressibility phenomenon of the sediment (Burland, 1990;Favre and Hattab, 2008) characterized by the compression index C c = 0.94. The observed paths, for both intact sediments, highlight the behaviour of a non-remoulded (intact) normally consolidated sediment, with a bend towards the stress s' v = 60 kPa located above the remoulded oedometric path, suggesting the beginning of breakage of cementation between ''grains'' and particles.…”
Section: Behaviour On Oedometric Stress Pathmentioning
confidence: 99%